Analisis Perhitungan Pajak Penghasilan Pasal 21 Atas Pendapatan Pegawai Pada Balai Kota Among Tani Kota Batu - Cindhy Amelia Putri; Zaki Bahrun Ni’am (Jurnal Ilmiah Wahana Pendidikan, 2023)
Taxation is one manifestation of the participation of citizens as taxpayers. Income tax article 21 is a tax imposed on tax subjects on income received for individuals in connection with the work/services of individuals received for one tax year. This study aims to determine the suitability of the imposition of income tax article 21 Among Tani City Hall Employees, Batu City with the provisions of the applicable tax regulations. Data collection techniques using 2 methods, namely the method of documentation and interview methods. The subjects of this study were employees at Among Tani City Hall, Batu City and the object of calculation was PPh Article 21. The data used was qualitative data, then the data would be analyzed using qualitative descriptive analysis by presenting an analysis of the calculation of PPh article 21 on Employee Income at Among City Hall Stone Town Farmer. The results of this study indicate that the analysis of the calculation of PPh Article 21 on Employee Income at the Batu City Hall shows that it is in accordance with Law Number 36 of 2008 concerning Income Tax and Regulation of the Minister of Finance Number 101/PMK.010/2016 concerning the amount of PTKP (Unaccountable Income). Tax).